Caulim do Morro do Felipe, baixo Rio Jari, estado do Amapá, contexto geológico e gênese - DUARTE, Adalciléo Lúcio de Souza (1995)
The kaolin district of Morro do Felipe, located in the northwestem part ofthe State of Amapá close to the Jari river, contains abaut 366.000 metric tons of high quality ore - This arca is composed ofseveral plateaus up to 250 m, dissected by narrow valleys. The weathenng mantle which covers the plateaus consists of six, well individualized horizons, that is, firom bottom to top: a) clayey sandstones of the Alter do Chão Formation ( upper Cretaceous ); b) a thick kaolin horizon; c) a ferrugmous duricrust; d) a nodular lateritic levd; e) a gravelly bauxitic levei and f) a clayey overburden or Belterra Clay. Such stmcture and the composition of the difíerent horizons suggest, for the alteration cover, a complex and polyphasic evolution which would include the following phases: 1) Ferrugmization of Alter do Chão sediments and formation of a ferruginous duricrustin depressions. 2) Degradation ofthe upper part ofthe duricrust 3) Desilication of the Alter do Chão sediments in the topographically higher situated zones and ofthe degradation products ofthe duricrust in the lower ones. Bauxitization. Aluminization in the depressions as the result of the partial dissoludon ofpreviously formed gibbsite. 4) Dismantling ofthe upper part of the profile and formation of eluvial (nodular levei) and coluviáL (gravelly levei) deposits. Demidalion in places of altered Alter do Chão sediments. 4 5) Reworking of the weathered Alter do Chão sedimente, transport as mass flows and deposition as a severa! meters thick cover. 6) Slow regional uplift , relative lowering of the watertable and progressive alteration ofthe sedimente that overlie the lateritic - bauxitic duricrust. Desilication ofthe sandy-clayey overbnrden and gradual transformation into thick, homogeneous and gLbbsite-nch latosol, the Belterra Clay. 7) In limited zones, accumulation of oiganic matter at surface. Due to acidic and reducing conditions, local deferrification of the Belterra Clay and concentraüon ofthe mobilized iron as thin lithified fiingès. 8) Later lowering ofthe water table and alteration at depth of the Alter do Chão sedimente The Morro do Felipe kaolin was formed "in situ", at the expense of clayey sedimente of the Alter do Chão Formation, after the overlying lateritic profile was formed and the proto- Belterra Clay sedimente were deposited. The low permeablility of the clayey sedimente seems to have been decisive in this process. Due to the limited water discharge, slightly acidic and weakly oxidizing to reducing conditions installed, that caused deferrification of those sedimente and degradation ofthe constiluenl minerais. The diminute size of the kaolinite crystallites, their disordered distríbuition, the lithification ofthe upper part ofthe kaolin and the pronounced structural disorder detected in the kaolinite suggest (re) crystallization of an amorphous silico-aluminous phase. Kaolinisation, which probably started in Upper Tertiary time, was a slow, highly depending on climatic variations and tectonic factors process. It is possible thatitis stül active nowadays. 5